2006
DOI: 10.1248/yakushi.126.117
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of the Opioidergic System and Nitric Oxide in the Analgesic Effect of Venlafaxine

Abstract: The noradrenalin and serotonin re-uptake inhibitor venlafaxine has an analgesic eŠect that is independent of its antidepressant activity; however, the mechanism of this eŠect remains to be elucidated. This study was performed to investigate the possible roles of the opioidergic system and nitric oxide (NO) pathway in the analgesic eŠect of venlafaxine. Eighty Wistar rats of both sexes were allocated to 10 groups. The hot plate test was used to assess the antinociceptive/ analgesic eŠect. The temperature of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…At the supraspinal level, milnacipran attenuates the increase in c-fos expression in the ACC in response to noxious stimulation [299]. Surprisingly, in contrast to duloxetine and milnacipran, venlafaxine produced antinociceptive effects in mice and rats in acute pain assessed in the hotplate test [303,304,311]. Although venlafaxine has a weak affinity for 5-HT and NE transporters in comparison with duloxetine and milnacipran, the reasons of such difference remain obscure.…”
Section: Monoamines Reuptake Inhibitors and Pain Preclinical Outcomesmentioning
confidence: 99%
“…At the supraspinal level, milnacipran attenuates the increase in c-fos expression in the ACC in response to noxious stimulation [299]. Surprisingly, in contrast to duloxetine and milnacipran, venlafaxine produced antinociceptive effects in mice and rats in acute pain assessed in the hotplate test [303,304,311]. Although venlafaxine has a weak affinity for 5-HT and NE transporters in comparison with duloxetine and milnacipran, the reasons of such difference remain obscure.…”
Section: Monoamines Reuptake Inhibitors and Pain Preclinical Outcomesmentioning
confidence: 99%
“…When high dose of naloxone (4mg/kg) was administered along with Venlafaxine (22mg/kg), analgesic activity decreased significantly. 16 This study shows that antinociceptive activity of Venlafaxine may be because of its action on opioid receptors like morphine or Pethidine.…”
Section: Discussionmentioning
confidence: 88%
“…VLF has also shown to relieve pain in patients with diabetic neuropathy, painful polyneuropathy and fibromyalgia [13,[32][33][34]. It has been reported that the somatodendritic 5-HT1A [16], k-or d-opioid [14], and a 2 -adrenergic [15] receptor systems are involved in the antinociception produced by VLF. Also, It has been reported that VLF produced dose-dependent antinociceptive activity in writhing test, which is consistent with our results [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…VLF mainly has a central site of action through interaction with monoamine transporter and also opioid and non-opioid receptor systems [14][15][16]. Therefore, the synergistic antinociceptive interaction between EA and VLF may occur at peripheral and/ or the central level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation